Bridge to terabithia eaudiobook - Paterson, Katherine (2009)
This beloved Newbery Medal-winning novel by bestselling author Katherine Paterson is a modern classic of friendship and loss. Jess Aarons has been practicing all summer so he can be the fastest runner in the fifth grade. And he almost is, until the new girl in school, Leslie Burke, outpaces him. The two become fast friends and spend most days in the woods behind Leslie's house, where they invent an enchanted land called Terabithia. One morning, Leslie goes to Terabithia without Jess and a tragedy occurs. It will take the love of his family and the strength that Leslie has given him for Jess to be able to deal with his grief. Bridge to Terabithia was also named an ALA Notable Children's Book and has become a touchstone of children's literature, as have many of Katherine Paterson's other novels, including The Great Gilly Hopkins and Jacob Have I Loved.